Kohabitasi Dalam KUHP 2023 Ternyata Tidak (Perlu) Dipidana - Kurniawan, Widhie; Sudarmanto, Kukuh; Sukarna, Kadi; Manurung, Mangaraja (Journal Juridisch, 2024)
This study aims to analyze the crime of cohabitation as an absolute complaint offense in practice before and after the enactment of Article 412 of Law No. 1/2023 concerning the Criminal Code. The background is the negative stigma against cohabitation in Indonesian society and the ambiguity of the law before the existence of explicit regulations. The urgency of this study is to provide legal certainty and avoid arbitrary handling of cohabitation cases. The research method used is normative juridical with a descriptive analysis approach, using secondary data from laws and regulations, literature, and dictionaries. The novelty of this study lies in the comprehensive analysis of the handling of cohabitation before and after the enactment of the new Criminal Code Law. The results of the study show that before Law No. 1/2023, the handling of cohabitation varied, ranging from customary sanctions to the application of adultery articles. With the enactment of the new Law as of January 2, 2026, cohabitation is regulated as an absolute complaint offense with limitations on complainants. In conclusion, although cohabitation now has a clear legal basis, its implementation still considers aspects of social balance and family resolution, similar to the concept of restorative justice. Customary law can still be applied in handling cohabitation, but requires government regulations as derivative rules for its implementation. Penelitian ini bertujuan untuk menganalisis tindak pidana kohabitasi sebagai delik aduan absolut dalam praktik sebelum dan setelah berlakunya Pasal 412 UU No. 1/2023 tentang KUHP. Latar belakangnya adalah stigma negatif terhadap kohabitasi di masyarakat Indonesia dan ketidakjelasan hukum sebelum adanya aturan eksplisit. Urgensi penelitian ini adalah untuk memberikan kepastian hukum dan menghindari penanganan sewenang-wenang terhadap kasus kohabitasi. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan deskriptif analisis, menggunakan data sekunder dari peraturan perundang-undangan, literatur, dan kamus. Kebaruan penelitian ini terletak pada analisis komprehensif terhadap penanganan kohabitasi sebelum dan setelah berlakunya UU KUHP baru. Hasil penelitian menunjukkan bahwa sebelum UU No. 1/2023, penanganan kohabitasi bervariasi, mulai dari sanksi adat hingga penerapan pasal perzinahan. Dengan berlakunya UU baru per 2 Januari 2026, kohabitasi diatur sebagai delik aduan absolut dengan limitasi pengadu. Kesimpulannya, meskipun kohabitasi kini memiliki dasar hukum yang jelas, penerapannya tetap mempertimbangkan aspek keseimbangan sosial dan penyelesaian kekeluargaan, mirip dengan konsep keadilan restoratif. Hukum adat masih dapat diterapkan dalam penanganan kohabitasi, namun memerlukan peraturan pemerintah sebagai aturan turunan untuk implementasinya.